How Drawing Changes (diségno, 2018)
Compared to just a few years ago, architects’ drawings today seem to have changed substantially, especially asregards a few important general questions which are, furthermore, closely related, some well-known, othersperhaps less: parametric design, BIM, Big Data and artificial intelligence. In the background, there is yet another revolution concerning authorship, of both drawings and, of course, projects. But let’s proceed in an orderly fashion. We can state, to begin with, that architectural drawing has enjoyed extraordinary historical stability over time.